The unalterable functions of journalists in view of the emerging multimedia job profiles. - Sánchez-García, P.; Campos-Domínguez, E.; Berrocal Gonzalo, S. (Revista Latina de Comunicación Social, 2015)
Introduction. This research article addresses the functions and job profiles of journalists in the new multimedia environment. Method. The study is based on a qualitative method, a state of the art review, and interviews to a sample of representatives of Spanish journalist associations. Results. There are coincidences between the academic and professional fields in relation to the inalterable features of journalists in view of the emerging multimedia job profiles. The article also offers an updating proposal for the classification of journalistic job profiles established by the Spanish National Agency for Quality Assessment and Accreditation (ANECA). Discussion. The new media environment highlights the need to review outdated concepts and keeps alive the scientific debate on the tasks that are being strengthened in the journalistic profession, as well as the need to redefine job and training profiles, which are still in going through a configuration phase in a changing media landscape.